(untitled) (Publicaciones en Ciencias y Tecnología, 2024)
The purpose was to evaluate the technical efficiency of the maintenance performed in a natural gas compressor plant owned by PDVSA Gas, located in the state of Monagas, Venezuela, during the years 2011 to 2022. The DEA method was used based on technical modifications to the OEE indicator and the impact of the maintenance actions implemented was determined. Initially, the years were assigned as DM, obtaining during the period 2011-2016 acceptable efficiencies (> 80 %), while during the period 2017 - 2022 the efficiencies decreased over time, which was considered as the critical period. A second phase for these years, the four motor-compressor units were considered as DMU, so during 2017-2019 the best efficiency (> 80 %) was presented by the unit called K1040, the other units presented a behavior not in accordance with the expected. In the period 2020-2022 there was evidence of a decrease in efficiency below 80 % in 66.7 % of the units. It is concluded that the application of the DEA method based on the modification of the OEE indicator to measure the technical efficiency of maintenance actions can be considered as a tool that presents results in accordance with the reality under study. Keywords: technical efficiency, DEA, maintenance, productivity, natural gas compressor plant.